Adding dendritic cell-immunotherapy for post-transplant hepatocellular carcinoma recurrence - Lee, Wei-Chen; Cheng, Chih-Hsien; Wu, Tsung-Han; Wang, Yu-Chao; Lee, Jin-Chiao; Hung, Hao-Chien; Lee, Chen-Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Chan, Kun-Ming (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) recurrence after liver transplantation is frequently multiple and extrahepatic, and with a poor prognosis. The therapeutic effects of current medications for post-transplant HCC recurrence are limited. This study assessed whether outcomes could be improved by adding dendritic cell (DC)immunotherapy to the treatment regimen.MethodsEleven patients treated with tyrosine kinase inhibitors and DC-immunotherapy for post-transplant HCC recurrence between 2020 and 2024 were included. DC were propagated from peripheral blood monocytes and pulsed with tumor lysate. Historical data of patients (n =23) with tyrosine kinase inhibitors for post-transplant HCC recurrence between 2009 and 2020 were collected as a reference.ResultsSeven male and four female patients were included in this study. The median (interquartile) tumor recurrence time after transplantation was 35.0 (7.4-55.3) months. The median number of DC-immunotherapy were 5 ranged from 3 to 10, and the median number of cells admitted was 29.5x106 cells ranged from 16.0 to 137.2 x106 cells. Responses to DC-immunotherapy included nine stable diseases and two progressive diseases. No adverse effects related to DC treatment were observed. The 1-, 2- and 3- year survival rates were 70.7%, 40.4%, and 40.4%, respectively, compared to 52.5%, 17.4%, and 8.7%, respectively, for patients treated with tyrosine kinase inhibitors only (p = 0.050).ConclusionDC immunotherapy is a safe treatment for transplant recipients with HCC recurrence. Adding DC-immunotherapy to the treatment regimen could prolong the survival of some patients.